2001
DOI: 10.1126/science.1063611
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis for Activity Differences Between Vancomycin and Glycolipid Derivatives of Vancomycin

Abstract: Small molecules that affect specific protein functions can be valuable tools for dissecting complex cellular processes. Peptidoglycan synthesis and degradation is a process in bacteria that involves multiple enzymes under strict temporal and spatial regulation. We used a set of small molecules that inhibit the transglycosylation step of peptidoglycan synthesis to discover genes that help to regulate this process. We identified a gene responsible for the susceptibility of Escherichia coli cells to killing by gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 21 publications
2
113
0
4
Order By: Relevance
“…Because glycopeptide analogues containing hydrophobic substituents on the vancosamino nitrogen retain activity against vanA strains when the binding pocket is damaged (7, 34 -36), the Williams model cannot explain the activity of these compounds. Therefore, we have proposed that certain glycopeptide analogues have a second mechanism of action that does not involve peptide binding (7,45). In this paper, we have presented kinetic evidence that chlorobiphenyl-vancosamino derivatives of vancomycin can inhibit PBP1b, the major transglycosylase in E. coli, even in the absence of substrate binding.…”
Section: Discussionmentioning
confidence: 95%
“…Because glycopeptide analogues containing hydrophobic substituents on the vancosamino nitrogen retain activity against vanA strains when the binding pocket is damaged (7, 34 -36), the Williams model cannot explain the activity of these compounds. Therefore, we have proposed that certain glycopeptide analogues have a second mechanism of action that does not involve peptide binding (7,45). In this paper, we have presented kinetic evidence that chlorobiphenyl-vancosamino derivatives of vancomycin can inhibit PBP1b, the major transglycosylase in E. coli, even in the absence of substrate binding.…”
Section: Discussionmentioning
confidence: 95%
“…Third, we focused on those remaining proteins that are predicted to be essential in E. coli because the OM is an essential organelle, and of unknown function-that is, they are encoded by ''y'' genes. (27)(28)(29). In contrast, Bl.…”
Section: Rationalementioning
confidence: 94%
“…These results indicate two possibilities; one is that the factors, which exhibit the moenomycin binding, but have no TGase consensus region, are present in S. aureus, and those are associated with moenomycin-resistance and/or vancomycin-intermediate susceptibility; the second is that factors other than moenomycin-binding proteins also affect the moeno- mycin-and/or vancomycin-susceptibility. It has been reported that vancomycin-derived modified carbohydrates inhibited the peptidoglycan biosynthesis without binding D-Ala-D-Ala molecules, and inhibited the transglycosylase activity in in vitro experiments (9,12). E. coli mutants showing resistance to these vancomycinderivatives also exhibited the moenomycin-resistance.…”
Section: Discussionmentioning
confidence: 99%